On the Same Wavelength: Exploring Team Neurosynchrony in Undergraduate Dyads Solving a Cyberlearning Problem With Collaborative Scripts. Issue 1 (21st January 2019) - Antonenko, Pavlo D.; Davis, Robert; Wang, Jiahui; Celepkolu, Mehmet
ABSTRACT: As teammates adjust their cognition and behavior, synchronizations of information can be observed across verbal, postural, and neurophysiological systems. This study explored the synchrony of mutually interacting brains, or team neurosynchrony, during cyber‐enabled collaborative problem solving. Mixed‐sex dyads defined and solved an authentic problem using either a social script or an epistemic script. Alpha‐band phase‐locking value, or the absolute value of the sum of the phase differences of electrodes at a particular time and frequency across a number of epochs, was used as a measure of team neurosynchrony. Contrary to our hypotheses, analyses revealed greater alpha‐band phase‐locking values between the central and parietal electrodes of dyad members in the epistemic script condition. Mean alpha phase‐locking values were positively correlated with collaborative problem solving performance and negatively correlated with time spent on the problem solving process, suggesting that epistemic scripts were more effective scaffolds of collaborative problem solving compared to social scripts in this study.